2000
DOI: 10.1128/mcb.20.14.4959-4969.2000
|View full text |Cite
|
Sign up to set email alerts
|

The 2′-5′ Oligoadenylate/RNase L/RNase L Inhibitor Pathway Regulates Both MyoD mRNA Stability and Muscle Cell Differentiation

Abstract: The 2-5 oligoadenylate (2-5A)/RNase L pathway is one of the enzymatic pathways induced by interferon. RNase L is a latent endoribonuclease which is activated by 2-5A and inhibited by a specific protein known as RLI (RNase L inhibitor). This system has an important role in regulating viral infection. Additionally, variations in RNase L activity have been observed during cell growth and differentiation but the significance of the 2-5A/RNase L/RLI pathway in these latter processes is not known. To determine the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 44 publications
1
75
0
2
Order By: Relevance
“…Studies of subcellular localization of RNase L showed that RNase L could be associated with polysomes [24], mitochondria [100], cytoskeleton [101] and nuclei [102], suggesting that RNase L could regulates the stability of different cellular RNA species in different cellular compartments. Conditional expression of RNase L showed that RNase L regulates MyoD mRNA stability and muscle cell differentiation [103]. RNase L in mitochondria regulates mitochondrial mRNA stability and possibly contributing to the antiproliferative activity of IFNs [100].…”
Section: ) Regulation Of Cellular Mrna Stabilitymentioning
confidence: 99%
“…Studies of subcellular localization of RNase L showed that RNase L could be associated with polysomes [24], mitochondria [100], cytoskeleton [101] and nuclei [102], suggesting that RNase L could regulates the stability of different cellular RNA species in different cellular compartments. Conditional expression of RNase L showed that RNase L regulates MyoD mRNA stability and muscle cell differentiation [103]. RNase L in mitochondria regulates mitochondrial mRNA stability and possibly contributing to the antiproliferative activity of IFNs [100].…”
Section: ) Regulation Of Cellular Mrna Stabilitymentioning
confidence: 99%
“…12 RNase L is an endoribonuclease which has little sequence specificity as it cleaves RNA 3 0 of UpNp nucleotides. 6,7 On the other hand, only a few cellular RNAs have been identified as regulated by RNase L: rRNA, 16 IFN-induced genes ISG43 and ISG15 mRNAs, 17 mitochondrial mRNAs, 12,18 MyoD mRNA during C2 myoblast differentiation 19 and PKR mRNA. 20 RNase L activity is regulated not only by 2-5A binding, but also by interaction with other proteins.…”
mentioning
confidence: 99%
“…This pathway is reviewed by Silverman and Bisbal in this same issue. In recent years, it has been accepted that RNase L participates in the degradation of selected cellular mRNAs [63][64][65][66][67]. Specifically, RNase L has been shown to downregulate PKR mRNA [64].…”
Section: The Role Of Ifn-regulated Rnase L and Pkr In The Post-transcmentioning
confidence: 99%
“…RNase L and its inhibitor RLI are sequentially induced during C2 cell line myoblast differentiation to myotubes [63]. Inhibition or over-expression of RNAse L prolongs or decreases MyoD mRNA half life, respectively [63].…”
Section: The Role Of Ifn-regulated Rnase L and Pkr In The Post-transcmentioning
confidence: 99%
See 1 more Smart Citation